Technostress among employees: a case study in International Islamic University Malaysia (IIUM) / Nur ‘Atikah Napis - Napis, Nur ‘Atikah (2019)
The aim of this study is to investigate influencing technostress among employees in International Islamic University Malaysia (IIUM). The advances in technology in recent years have increased for decreased the levels of technostress that users have. This study also shows the effect of technostress to the users. A few set of questions will be sent to determine the technostress creators and also the levels of technology addiction the participants have. The results from these question sets will show if there is any correlation between technostress and techno-overload, technoinvasion, techno-complexity, techno-insecurity and techno-uncertainty. This study concluded that with the rapid advancements in technology even during socially unacceptable times, which can upset people around them. Overusing technology may be an addiction that has to be acknowledged and managed by the user.